EXPERIENCE OF THE EARLY SCREENING PROGRAMS FOR GESTATIONAL DIABETES MELLITUS IN UGANDA. A CROSS-SECTIONAL STUDY. - Serunjogi, David; Namakula , Matilda; Nalabuka, Hellen; Murungi, Sadiq; Mutunzi, Roggers; Namigadde, Josephine (Student’s Journal of Health Research Africa, 2024)
Background Gestational diabetes mellitus (GDM), is the most common metabolic disorder of pregnancy. The study aims to assess the experience of the early screening programs for GDM and Myths about GDM screening, in Uganda. Methodology A qualitative field analysis study was carried out at the antenatal care department in Wakiso district, Entebbe municipality at Entebbe Regional Referral Hospital. Eight (9) women (04 without GDM, and 5 without GDM), and 06 Health workers were interviewed using open-ended questionnaires. Results Most mothers came to antenatal care without expecting that among things they would do, would include early screening for GDM. Most mothers said that they were happy to have been screened for diabetes during pregnancy and know their status. The program helped mothers to continue living a healthy lifestyle including following the recommendations given by the health workers. They reported not knowing that after diagnosis, the high blood sugar levels would eventually return to normal after delivery. Mothers developed a lot of theories and myths on how one can know if they have high blood sugar levels or not during pregnancy. A Mother said, “Because we were told to check our urine every morning to see if it was sweet or sour. And if it was found sweet that would mean you were diabetic and if sour then you were not diabetic.’’ Conclusion The results from this public health field analysis show that the early screening program had a valuable impact on both the mothers who took part and the healthcare providers who participated in the implementation of the program. Recommendation There is a need for public health professionals in Uganda to develop information, education, and communication materials about GDM.